Maxine Hong Kingston's Evolution From Autobiographical Prose to Poetry - Haddeman, Betsabe Linda (My University, 2015)
My first chapter is an overview of Transactional Reader Response theory. Critics of Transactional Reader Response theory claim that there is a relationship between text and the reader. I discuss how Transactional Reader Response theory can be applied to Maxine Hong Kingston's works. Transactional Reader Response theory allows the reader to create a personal connection with a text. In reading I Love a Broad Margin To My Life a reader will have to create meaning with the poetic text. Chapter Two is about how Kingston has written her first narrative of the Fa Mu Lan story in The Woman Warrior: A Girlhood Among Ghosts. Critics of The Woman Warrior only wrote about how the story wasn't Chinese anymore rather than how meaning is created. In I Love a Broad Margin To My Life, Kingston changed the story of Fa Mu Lan, and now it represents a more believable narrative that is related to American war stories today. The final chapter discusses Kingston's poetry and how it creates for the reader an opportunity to relate to the text in a personal way and create a response. This chapter also discusses how Kingston has transformed from a prose writer to a poet and how the transformation has freed her to create stories. This book of poetry has inspired me to respond to the narrative to try to understand and interpret the way I felt about the story of Fa Mu Lan. I understand mother and child relationships in a unique way because I was adopted as a young child. Kingston carried over the Fa Mu Lan story into a new generation in a simple way for her readers to make connections to the text through their own experiences.
Keywords: Transactional reader response theory; Reader-response criticism; Literary criticism